Area of Damage and Distribution of Occurrence The Red Root Disease in Gunung Walat University Forest, Sukabumi LUAS SERANGAN DAN SEBARAN KEJADIAN PENYAKIT AKAR MERAH DI HUTAN PENDIDIKAN GUNUNG WALAT, SUKABUMI - Achmad .; Elis Nina Herliyana; Deasy Putri Permatasari (Jurnal Silvikultur Tropika, 2016)
Gunung Walat University Forest (GWUF) is known as education and research area. GWUF has a lot of homogen areas, therefore these area was attacked easily by disease, and of course this red root disease. Red root disease is caused by Ganoderma sp. and this disease can spread for plant to another plant in a lot of ways. The objectives of the study were to review the spreading of Ganoderma sp. that cause red root disease which attacked the forest tree in GWUF and also to identified species of Ganoderma sp. in visual way. The results showed that there were Ganoderma sp. in GWUF which spread in a lot of areas and also there were 7 species of Ganoderma sp. in Agathis and Pinus block, 5 species of them are attack Agathis block and 2 another species are attack Pinus block. Each Ganoderma sp. has different morphologies characteristic.Key words: Agathis sp., Ganoderma sp., GWUF, Pinus sp., red root disease